Heuristics as a learning methodology in processes in the sales area in ecuadorian commercial companies. - Yagual Velastegui, Alfredo Marcel; Coronel Pérez, Iván Ariolfo; Ortiz Luzuriaga, Daniel (Revista Universidad de Guayaquil, 2019)
The present article intends to analyze heuristics as a learning methodology in sales processesin commercial companies. That is, as a method of research and evaluation, in order to designand execute a learning methodology. For this, the methodology instruments were contrastedwith heuristic criteria as a means of resolving conflicts of a company in the sales area. After adocumentary analysis it was possible to conclude that they are a series of cognitive stages inteaching-learning that allow collaborators and managers to interpret the changes ofenvironments that companies face on a day-to-day basis.
Keywords: Heuristics; Business; Administration; Learning